A 269‐278 GHz voltage‐controlled oscillator with uniform output power of 5 dBm. Issue 4 (31st January 2019) - Choi, Seung Ho; Yi, Changhwan; Kim, Moonil
Abstract: A terahertz oscillator design with an emphasis on the output power performance is presented. The 270‐GHz oscillator fabricated using InP 250‐nm DHBT technology adopts a common‐base cross‐coupled configuration. The design focus is on the input varactor termination by utilizing simulated power and frequency load‐pull contours. The measurement results show an improved peak output power of 5.8 dBm with an outstanding power variation of only 0.8 dB while maintaining moderate frequency‐tuning range of 269‐278 GHz.